Biocompatibility of gold nanoparticles and their endocytotic fate inside the cellular compartment: a microscopic overview - Shukla, Ravi; Bansal, Vipul; Chaudhary, Manakshi; Basu, Atanu; Bhonde, Ramesh R.; Sastry, Murali (Langmuir, 2005)
Macrophages are one of the principal immune effector cells that play essential roles as secretory, phagocytic, and antigen-presenting cells in the immune system. In this study, we address the issue of cytotoxicity and immunogenic effects of gold nanoparticles on RAW264.7 macrophage cells. The cytotoxicity of gold nanoparticles has been correlated with a detailed study of their endocytotic uptake using various microscopy tools such as atomic force microscopy (AFM), confocal-laser-scanning microscopy (CFLSM), and transmission electron microscopy (TEM). Our findings suggest that Au(0) nanoparticles are not cytotoxic, reduce the production of reactive oxygen and nitrite species, and do not elicit secretion of proinflammatory cytokines TNF-alpha and IL1-, making them suitable candidates for nanomedicine. AFM measurements suggest that gold nanoparticles are internalized inside the cell via a mechanism involving pinocytosis, while CFLSM and TEM studies indicate their internalization in lysosomal bodies arranged in perinuclear fashion. Our studies thus underline the noncytotoxic, nonimmunogenic, and biocompatible properties ofgold nanoparticles with the potential for application in nanoimmunology, nanomedicine, and nanobiotechnology.

Imaging the interaction between dengue 2 virus and human blood platelets using atomic force and electron microscopy - Ghosh, Kanjaksha; Gangodkar, Shobha; Jain, Preksha; Shetty, Shrimati; Ramjee, Sandhya; Poddar, Pankaj; Basu, Atanu (Journal of Electron Microscopy, 2008)
Thrombocytopenia is frequently associated with dengue virus infection. Host factors such as anti-platelet immunopathogenic processes have been implicated in the origin of dengue-associated thrombocytopenia but the role of dengue virus in directly interacting with platelets and altering their hemostatic property remains incompletely understood. In the present study, we examined the effect of dengue 2 virus on the morphology and physiological activation profile of normal human platelets using atomic force microscopy, electron microscopy and flowcytometry. Platelets obtained from healthy donors were exposed to a cell culture-adapted 10(4) LD(50) dengue 2 virus isolate in vitro and the subsequent effect on morphology and activation biology studied. Our results show that dengue 2 virus exposure at doses comparable to natural viremic states in human infections can activate platelets with an increase in P-selectin expression and fibrinogen-binding property. Atomic force, scanning and transmission electron microscopy also showed typical activation-related morphological changes such as altered platelet membrane architecture, degranulation, presence of filopodia and dilatation of the open canalicular system in the dengue 2 virus-exposed platelets but not in the controls. Importantly, Japanese encephalitis virus exposure at the same dose did not activate platelets or show any morphological changes. Our findings suggest that dengue 2 virus may directly interact with and activate platelets - an event that might be important in the origin of dengue-associated thrombocytopenia. Detailed molecular characterization of this effect might provide key knowledge toward better prophylaxis of the hemostatic complications of dengue disease.
Keywords: AFM; dengue virus; Electron microscopy; platelet